2015
DOI: 10.1002/2014jb011458
|View full text |Cite
|
Sign up to set email alerts
|

On magnetic estimation of Earth's core angular momentum variation

Abstract: We study systematically the estimation of Earth's core angular momentum (CAM) variation between 1962.0 and 2008.0 by using core surface flow models derived from the recent geomagnetic field model C 3 FM2. Various flow models are derived by changing four parameters that control the least squares flow inversion. The parameters include the spherical harmonic (SH) truncation degree of the flow models and two Lagrange multipliers that control the weights of two additional constraints. The first constraint forces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Here we do not deny that the mechanism suggested by Ding and Chao (2018a) may be inappropriate, but there are still some doubtful points in Gillet et al (2020). For example, 1) they used the internal loading Love numbers from Dumberry and Bloxham (2004), which are different from either of those suggested by Fang et al (1996) and Greff-Lefftz et al (2004); 2) the dynamical pressure at the surface of the core they used came from the core flow models which were inverted from geomagnetic observations; however, such core flow models were obtained based on a few assumptions, and different assumptions may obtain different results (e.g., Finlay et al, 2010;Asari and Wardinski, 2012;Gross, 2015;Homle, 2015); 3) the process for inverting the core flow model from the geomagnetic observations involves fitting the fluctuations in the observations with spline curves, while a spline curve may be consisted by different periodic/quasi-periodic oscillations related to different harmonic coefficients; simply spline curve fitting may cause different Ylm-related signals to leak into a given Yl′m′ term, and therefore obtain inappropriate results and explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we do not deny that the mechanism suggested by Ding and Chao (2018a) may be inappropriate, but there are still some doubtful points in Gillet et al (2020). For example, 1) they used the internal loading Love numbers from Dumberry and Bloxham (2004), which are different from either of those suggested by Fang et al (1996) and Greff-Lefftz et al (2004); 2) the dynamical pressure at the surface of the core they used came from the core flow models which were inverted from geomagnetic observations; however, such core flow models were obtained based on a few assumptions, and different assumptions may obtain different results (e.g., Finlay et al, 2010;Asari and Wardinski, 2012;Gross, 2015;Homle, 2015); 3) the process for inverting the core flow model from the geomagnetic observations involves fitting the fluctuations in the observations with spline curves, while a spline curve may be consisted by different periodic/quasi-periodic oscillations related to different harmonic coefficients; simply spline curve fitting may cause different Ylm-related signals to leak into a given Yl′m′ term, and therefore obtain inappropriate results and explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Chao (2017) further equated the MICG axial torsional libration to the steady SYO in ΔLOD and calculated the corresponding MIGG strength (torsion constant), which lies in the range given by Davies et al (2014) from a broad range of viscous mantle flow models with density anomalies inferred from seismic tomography. Gillet et al (2010) explained the SYO signal by the fast torsional waves throughout the fluid outer core based on the core angular momentum (CAM) variation, while Asari and Wardinski (2012) suggested that the CAM variation is not yet sufficient for arguing that Earth's 6 years CAM oscillation is robustly resolved by magnetic observation. Gillet et al (2015) showed that the ΔLOD at 4 to 9.5 years periods could be explained by torsional waves, which may be triggered by the nonlinear interaction between the magnetic field and sub-decadal nonzonal motions within the fluid outer core.…”
Section: Introductionmentioning
confidence: 99%